Status of zoonotic disease research in refugees, asylum seekers and internally displaced people, globally: A scoping review of forty clinically important zoonotic pathogens. - Regina Oakley; Nadja Hedrich; Alexandra Walker; Habtamu Merha Dinkita; Rea Tschopp; Charles Abongomera; Daniel H Paris (PLoS Neglected Tropical Diseases, 2024)
Background At the end of 2022, there were over 108 million forcibly displaced people globally, including refugees, asylum seekers (AS) and internally displaced people (IDPs). Forced migration increases the risk of infectious disease transmission, and zoonotic pathogens account for 61% of emerging and re-emerging infectious diseases. Zoonoses create a high burden of disease and have the potential to cause large-scale outbreaks. This scoping review aimed to assess the state of research on a range of clinically relevant zoonotic pathogens in displaced populations in order to identify the gaps in literature and guide future research. Methodology / principal findings Literature was systematically searched to identify original research related to 40 selected zoonotic pathogens of interest in refugees, AS and IDPs. We included only peer-reviewed original research in English, with no publication date restrictions. Demographic data, migration pathways, health factors, associated outbreaks, predictive factors and preventative measures were extracted and synthesized. We identified 4,295 articles, of which 347 were included; dates of publications ranged from 1937 to 2022. Refugees were the most common population investigated (75%). Migration pathways of displaced populations increased over time towards a more complex web, involving migration in dual directions. The most frequent pathogen investigated was Schistosoma spp. (n = 99 articles). Disease outbreaks were reported in 46 publications (13.3%), with viruses being the most commonly reported pathogen type. Limited access to hygiene/sanitation, crowding and refugee status were the most commonly discussed predictors of infection. Vaccination/prophylaxis drug administration, surveillance/screening and improved hygiene/sanitation were the most commonly discussed preventative measures. Conclusions / significance The current research on zoonoses in displaced populations displays gaps in the spectrum of pathogens studied, as well as in the (sub)populations investigated. Future studies should be more inclusive of One Health approaches to adequately investigate the impact of zoonotic pathogens and identify transmission pathways as a basis for designing interventions for displaced populations.